Synthesis of graphene oxide via electrochemical exfoliation of graphite from batteries - Araújo, Georgia Jully Bezerra; Morais, Camila da Costa de; Melo, Livia Islanny Fernandes de; Morais, Crislânia Carla Oliveira; Magalhães, Keurison Figueiredo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
In recent years, there has been a significant increase in the amount of solid waste, including dry cell batteries. Although many countries have adopted regulations for recycling these materials, in many regions, batteries continue to be discarded in household waste, which can cause environmental problems. During battery dismantling, the graphite rods inside are not reused and end up being disposed of in landfills or incinerated. If incinerated, they are converted to CO2, further damaging the environment. Graphene obtained from graphite exfoliation demonstrates exceptional properties, presenting high electrical conductivity and thermal resistance. However, graphene synthesis faces technical difficulties and high costs, and electrochemical exfoliation is a promising technique for minimizing these problems. This study evaluated the use of graphite rods from new and used dry batteries to produce graphene oxide (GO) by electrochemical exfoliation, with the aim of reducing the disposal of solid waste. (Ferella; Michelis; Vegliò, 2008). The study began with the removal and preparation of graphite rods from new and used AA batteries (1.5 V). First, the rods were sanded and immersed in a 5% H2SO4 solution to remove the remaining electrolytic paste and were then used as electrodes in the manufacture of graphene oxide (GO). The synthesis optimization was carried out with new rods, and the optimized experimental condition was applied for the tests with the used rods. For the synthesis, the rods were immersed in 50 mL of H2SO4 solution, at different concentrations (0.1, 0.2 and 0.3 mol L−1). Exfoliation was performed in direct current and different voltages and times were evaluated. The produced material was filtered, washed until reaching neutral pH and dried in an oven. For characterization, the samples were dispersed in ultrapure water and analyzed by UV-Visible spectrophotometry. To evaluate the applicability of GO, a cyclic voltammetry study at 50 mV/s was carried out, in which a glassy carbon electrode (GCE) modified with the produced GO (GCE/GO) was used as the working electrode. The absorption spectra revealed bands between 220 and 230 nm, characteristic of GO, attributed to the π-π* transitions of the C=C bonds of the aromatic rings in the material, and a soft band between 350 and 450 nm, indicating n-p* transitions attributed to the presence of carbonyl groups in the GO nanosheets (Protopapa et al., 2022). The results showed that the synthesis in H2SO4 0.1 mol L−1 was more efficient and the produced GO was used to modify the surface of an GCE, which was tested in a 7.0 x 10−4 mol L−1 solution of potassium ferrocyanide in 0.10 mol L−1 of KCl. The cyclic voltammograms showed a significant increase in the redox peak currents of the ferro/ferricyanide pair, as well as a decrease in ΔEp, when compared to the results obtained using the GCE without modification. This behavior highlights the effectiveness of GCE/GO as an electrochemical sensor platform, which is attributed to the high electrocatalytic capacity, excellent support for electron transfer, and high surface area of ​​GO. This study demonstrates the potential of the electrochemical approach for both the production of GO and the use of ECV/GO as a platform for the development of sensors; it also shows the relevance of continuing research aimed at improving work with graphite from used batteries and the use of solid waste as a form of environmental protection.